The implementation of uncertainty evaluation model in manufacturability analysis system for miniature machine tool - Abdul Shukor, Syaimak (Cranfield University Press, 2013)
The development of Manufacturability Analysis System for micro-machining domain (MicroMAS) is intended to address the need of the 4-axis Miniature Machine Tool (MMT) that require such system to assist the user in generating micro-component through manufacturability evaluation. One of the manufacturability aspects being assessed is the impacts from Uncertainty Evaluation Model (UEM) analysis that analyse the influence of the errors stemmed from the MMT construction on the geometrical accuracy of the machined micro-parts. The model has allowed a methodology for the errors in a custom-made MMT to be predicted and to further understand the origin of the errors on the machined micro-part. This paper reports on the implementation of UEM in the development of MicroMAS. Therefore, the results from uncertainty evaluation towards the MMT were integrated in the database which are interactively searched based on IF-THEN clauses in order to determine which rules satisfy the requirements expressed via inputs.
Keywords: manufacturability analysis system; uncertainty evaluation model; miniature machine tool